2012
DOI: 10.1089/biores.2012.0211
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of Three-Dimensional Fibrin Constructs Corresponds to Fibrinogen and Thrombin Concentrations

Abstract: Research in the last few years have focused on the use of three-dimensional (3D) fibrin construct to deliver growth factors and cells. Three-dimensional construct permeability and porosity are important aspects for proper nutrient uptake, gas exchange, and waste removal—factors that are critical for cell growth and survival. We have previously reported that the mechanical strength (stiffness) of 3D fibrin constructs is dependent on the fibrinogen and thrombin concentration. In this study, we established two ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 23 publications
1
41
0
2
Order By: Relevance
“…Studies have shown how gelatin or elastin can be incorporated to decrease biodegradability and improve structural strength [35]. Additionally, growth factors and enzyme-specific peptides can also be incorporated to influence biodegradability and matrix permeability in a similar way to previously discussed natural scaffolds [36,39,40] (Figure 2). This ability to control and manipulate the architecture of synthetic scaffolds, as well as tune biodegradability and strength, has made synthetic scaffolds more favorable over natural ones in many applications [35,36,40] (Table 2).…”
Section: Synthetic Scaffoldsmentioning
confidence: 85%
See 2 more Smart Citations
“…Studies have shown how gelatin or elastin can be incorporated to decrease biodegradability and improve structural strength [35]. Additionally, growth factors and enzyme-specific peptides can also be incorporated to influence biodegradability and matrix permeability in a similar way to previously discussed natural scaffolds [36,39,40] (Figure 2). This ability to control and manipulate the architecture of synthetic scaffolds, as well as tune biodegradability and strength, has made synthetic scaffolds more favorable over natural ones in many applications [35,36,40] (Table 2).…”
Section: Synthetic Scaffoldsmentioning
confidence: 85%
“…A better solution comes in the form of other naturally-occurring matrices that can be created in the laboratory [36]. Fibrin scaffolds serve as a common favorable matrix for tissue engineering as they satisfy most of the key requirements [39]. Fibrin acts as a perfect natural matrix for cell proliferation that can be easily tuned by adjusting the concentrations of the thrombin and fibrinogen co-factors [39].…”
Section: Ecm Scaffolds For Organ Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel experimental setups have been developed to probe the diffusion of insulin-like growth factor I (IGF-I) and ribonuclease through fibrin hydrogels of low density (2.25 mg/mL) and low volume fraction (0.27 vol% of a dry hydrogel), yielding diffusivity values comparable to that in water and pointing to a negligible influence of the open, fibrous network [41]. Moreover, variations in fibrinogen (5-20 mg/mL) and thrombin (2-20 U/mL) concentrations have been shown to affect the permeability of fibrin hydrogels and the release of dextran solutes (3 and 70 kDa) [42]. However, to the best of our knowledge, a quantitative analysis assessing the effect of specific fibrin hydrogel architectures on solute diffusivity over a wide range of pore sizes has not been tested so far.…”
Section: Introductionmentioning
confidence: 99%
“…36 Fibrin scaffolds serve as a common favorable matrix for tissue engineering as they satisfy most of the key requirements. 39 Fibrin acts as a perfect natural matrix for cell proliferation that can be easily tuned by adjusting the concentrations of the thrombin and fibrinogen co-factors. 39 However, while natural scaffolds offer great versatility and biocompatibility, they are limited in structural strength and longevity.…”
mentioning
confidence: 99%